2023
DOI: 10.3390/toxins15030190
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Antibiotics in Managing Bacterial Infections on Bite Sites following Snakebite Envenomation

Abstract: Snakebite envenomation (SBE) is a life-threatening medical emergency with a high mortality rate. Common secondary complications following SBE, such as wound infections, are significant due to their impact on worsening local tissue damage and causing systemic infection. Antivenoms are not effective to treat wound infections following SBE. Moreover, in several rural clinical settings, broad-spectrum antibiotics are often used without clear guidelines or based on limited laboratory data, resulting in undesirable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The description of wound infection associated with SBE is mentioned in many articles, and a considerable percentage of patients developed this complication. Soft tissue infection such as cellulitis or abscess formation was described in 10% to 25% of patients in most studies [ 6 , 9 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], but its occurrence could be higher depending on the severity of envenoming [ 23 , 24 ]. In contrast, in some settings the prevalence of infections in SBE patients is lower [ 25 , 26 , 27 ], probably related to the type of envenoming and management received by patients in these settings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The description of wound infection associated with SBE is mentioned in many articles, and a considerable percentage of patients developed this complication. Soft tissue infection such as cellulitis or abscess formation was described in 10% to 25% of patients in most studies [ 6 , 9 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], but its occurrence could be higher depending on the severity of envenoming [ 23 , 24 ]. In contrast, in some settings the prevalence of infections in SBE patients is lower [ 25 , 26 , 27 ], probably related to the type of envenoming and management received by patients in these settings.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the incidence of infection was not reduced in patients receiving antibiotics compared to those who did not receive them [ 21 , 29 , 33 ]. Other studies also argue against the use of prophylactic antibiotics in SBE ( Table 1 ) [ 23 , 25 , 26 , 37 ]. Thus, there is a predominant view in the reviewed literature that the prophylactic administration of antibiotics in SBE is not warranted and that they should be used only when there is clinical or bacteriological evidence of infection.…”
Section: Resultsmentioning
confidence: 99%
“…Tissue necrosis around the bite site may require operative interventions such as local debridement and fasciotomy along with possible amputation where attempts at limb salvage are not viable or successful [18,19]. A wide range of antibiotics is used to combat bacterial infections arising from SBE and patients who experience acute kidney injury often need dialysis [20,[24][25][26]. Thus, a notable variety of treatment methods is required to counteract the broad spectrum of clinical effects induced by SBE.…”
Section: Introductionmentioning
confidence: 99%